2015
DOI: 10.3109/14767058.2015.1063608
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of intralobar pulmonary sequestration during the pregnancy: report of two cases through relationships between mass and fetal biometry and review of the literature

Abstract: Intralobar pulmonary sequestration is a rare bronchopulmonary malformation consisting of a non-functioning lung mass that receives its arterial blood supply from systemic circulation and that does not adequately communicate with the tracheobronchial tree through a normal bronchus. These sequestrations account for 1.1-1.8% of all lung resections. Herein we present two clinical cases with a prenatal diagnosis of pulmonary sequestration using ultrasound and magnetic resonance imaging. Pulmonary images indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This observation agrees with previously published studies on this minimally invasive ultrasound-guided fetal surgery technique [3,[5][6][7][8][9][10]19] and with previously reported cases of spontaneous lung mass resolution during fetal monitoring secondary to unexpected strangulation of the feeding artery [3,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…This observation agrees with previously published studies on this minimally invasive ultrasound-guided fetal surgery technique [3,[5][6][7][8][9][10]19] and with previously reported cases of spontaneous lung mass resolution during fetal monitoring secondary to unexpected strangulation of the feeding artery [3,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…Searches of Medline and Embase were performed to identify all studies in the English language that reported on the expectant and invasive management of fetuses diagnosed with BPS. In the case of fetuses managed expectantly, only reports of at least two fetuses were considered [ 1 , 10 , 17 , 18 , 19 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%